1994
DOI: 10.1063/1.112555
|View full text |Cite
|
Sign up to set email alerts
|

Native defect related optical properties of ZnGeP2

Abstract: We present photoluminescence, photoconductivity, and optical absorption spectra for ZnGeP2 crystals grown from the melt by gradient freezing and from the vapor phase by high pressure physical vapor transport (HPVT). A model of donor and acceptor related subbands in the energy gap of ZnGeP2 is introduced that explains the experimental results. The emission with peak position at 1.2 eV is attributed to residual disorder on the cation sublattice. The lower absorption upon annealing is interpreted in terms of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…4, when annealing at 600 1C for 300 h in vacuum, the transmittance in the near 1 mm region increased about 10%, while decreased about 5-10% in the region beyond 1.6 mm. It was reported that the incomplete transition from zinc-blende phase to chalcopyrite phase on cooling through 950 1C during growth makes the co-existence of the ordered and disordered regions in the crystals [19,20], especially for the Ge Zn antisite defects [17,18]. Setzler thought these acceptor defects may indirectly induce the absorption near 1 mm [8].…”
Section: Thermal Annealing Processmentioning
confidence: 98%
See 1 more Smart Citation
“…4, when annealing at 600 1C for 300 h in vacuum, the transmittance in the near 1 mm region increased about 10%, while decreased about 5-10% in the region beyond 1.6 mm. It was reported that the incomplete transition from zinc-blende phase to chalcopyrite phase on cooling through 950 1C during growth makes the co-existence of the ordered and disordered regions in the crystals [19,20], especially for the Ge Zn antisite defects [17,18]. Setzler thought these acceptor defects may indirectly induce the absorption near 1 mm [8].…”
Section: Thermal Annealing Processmentioning
confidence: 98%
“…Despite other measurements such as photoluminescence (PL) [18], Rietveld refinement of XRD patterns [19,20] and magnetic circular dichroism of the absorption (MCDA) [21] were also used to identify the type of defects existed in as-grown ZnGeP 2 crystals as well as their contributions to the broad absorption band, limited works on the effect of different thermal anneal conditions, which may change the concentrations of different types of point defects have been done. In this paper, a crack-free ZnGeP 2 single crystal of diameter^8 and 40 mm length was grown using accelerated crucible rotation technique (ACRT) Bridgman method, and the effect of thermal annealing in different atmospheres on the infrared absorption was studied using vis-NIR transmission spectrum and IR transmission spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Results of photoluminescence experiments help to further connect these defects seen by EPR to the near infrared absorption. While PL spectra in ZnGeP 2 are often complex, 8 measurements taken on our samples indicate only two dominant emission bands at low temperature. Figure 2(a) shows PL spectra taken at 4.8 K with a polarizer placed parallel and perpendicular to the crystal c axis.…”
Section: A Epr and Pl Studiesmentioning
confidence: 99%
“…However, stable growth of the perfect ZGP crystal with high optical quality is very difficult due to the physical and chemical properties of this material. Firstly, ZGP is a complex ternary system, and contains two volatile components, Zn and P, with high vapor pressure at the melting temperature of 1027 1C, which can result in component deviations from stoichiometry not only in the process of polycrystalline synthesis but also in the growth process of ZGP single crystal; deviations from stoichiometry can lead to the formation of large magnitude of point defects, such as zinc vacancy (V Zn ), phosphorus vacancy (V P ) and Ge-Zn substitutional defect (Ge Zn ), which mainly result in high optical absorption in the range of 0.65-2.5 mm as mentioned in some literatures [1,3,[7][8][9][10][11][12]. Secondly, the vapor pressure of phosphorus is very high above its melting point.…”
Section: Introductionmentioning
confidence: 98%